Causes Of Consumptive Behavior Of Housewives In The Phenomenon Of National Online Shopping Day (Harbolnas) (Case Study Of Parents Of Students At Sdn 060 Raya Barat Bandung, Indonesia) - Sopiani, Siti Sopia; Nurdin, Muhamad Fadhil; Fedryansyah , Muhammad (GoAcademica Research & Publishing, 2024)
The phenomenon of harbolnas is still an interesting issue to discuss. Harbolnas is an annual activity jointly initiated by six major e-commerce companies in Indonesia since December 12, 2012, which is National Online Shopping Day in Indonesia. The development of online shopping media is in line with the increasing consumptive nature in society, especially for women who are targeted. This can make